2011
DOI: 10.1038/jid.2011.185
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Double-Stranded RNA Induces TSLP via an Endosomal Acidification- and NF-κB-Dependent Pathway in Human Keratinocytes

Abstract: Double-stranded RNA (dsRNA) causes keratinocytes to release thymic stromal lymphopoietin (TSLP), which plays a key role in allergic diseases. Endosomal Toll-like receptor 3 (TLR3) and cytosolic RIG-like receptors (RLRs) and PKR have been reported to recognize dsRNA. Here, we demonstrate that dsRNA induces TSLP in keratinocytes via an endosomal acidification-dependent and NF-κB-mediated pathway. After treatment with pharmacologic inhibitors or transfection with small interfering RNAs (siRNAs), primary human ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 35 publications
4
56
0
Order By: Relevance
“…Like bacterial skin infections, AD patients are also susceptible to viral skin infection [23]. However, as compared to bacterial skin infections, viral skin infections are relatively less common in AD patients.…”
Section: The Role Of Viral Skin Infections In Admentioning
confidence: 97%
See 1 more Smart Citation
“…Like bacterial skin infections, AD patients are also susceptible to viral skin infection [23]. However, as compared to bacterial skin infections, viral skin infections are relatively less common in AD patients.…”
Section: The Role Of Viral Skin Infections In Admentioning
confidence: 97%
“…Further studies of TLR functions and MDSC are needed in AD. Stimulation of TLR-3 by double-stranded RNA released from damaged epithelial cells leads to an increased production of thymic stromal lymphopoietin (TSLP) from keratinocytes [23]. TSLP is an IL-7-like cytokine that is highly expressed in AD lesions [24].…”
Section: Pathogenesis Of Admentioning
confidence: 99%
“…In primary human keratinocytes, we recently demonstrated that ligands for some Toll-like receptors (TLRs) (polyI:C for TLR3 [19,20], diacylated lipopeptide FSL-1 and Staphylococcus aureus membrane for TLR2-TLR6 [21], and flagellin for TLR5 [22]) upregulate the expression of the TSLP transcript and induce the release of TSLP. Proinflammatory cytokines such as TNF-a and the T H 2 cytokines IL-4 and IL-13 synergistically induce the release of TSLP in human skin explants [23] and upregulate the TLR liganddependent release of TSLP in primary human keratinocytes [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Proinflammatory cytokines such as TNF-a and the T H 2 cytokines IL-4 and IL-13 synergistically induce the release of TSLP in human skin explants [23] and upregulate the TLR liganddependent release of TSLP in primary human keratinocytes [19][20][21][22]. In mice, topical application of vitamin D receptor (VDR) agonists, calcitriol (1,25-dihydroxyvitamin D 3 , the active form of vitamin D 3 ) and its analog MC903 (calcipotriol; Dovonex), induces the expression of TSLP in epidermal keratinocytes and triggers an atopic dermatitis-like inflammation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Double-stranded RNA released from damaged epithelial cells may stimulate Toll-like receptor (TLR) 3, leading to the production of TSLP from keratinocytes (29). Deletion of a disintegrin and metalloproteinase 17 (ADAM 17), a transmembrane metalloproteinase that cleaves cell surface proteins and maintains barrier homeostasis, in murine keratinocytes has been shown to result in skin barrier defects and chronic dermatitis in mouse models (30,31).…”
Section: Keratinocyte Dysfunctions In Admentioning
confidence: 99%